Bilingualism as a gateway: Student perceptions on language and internationalisation - María Elena Gómez-Parra (Studies in English Language and Education, 2026)
This study explores student perceptions of the role that language abilities, particularly English and other foreign languages, play in facilitating internationalisation and global engagement. While extensive research has examined the impact of language proficiency on the opportunities to study abroad, there remains a limited understanding of how linguistic skills influence broader aspects of international mobility, including travel, living, and intercultural experiences across various contexts. Guided by a quantitative cross-sectional survey design, data were collected through a validated questionnaire administered to 3246 bilingual and non-bilingual students across diverse educational programmes online, and were analysed through Jamovi 2020, v. 1.2. The findings revealed that students, with particularly strong perceptions among those enrolled in bilingual education programmes, highly valued foreign language skills as vital for building self-confidence, motivation, and readiness for international experiences, while also showing differences between bilingual and non-bilingual learners. English, in particular, was perceived to hold a preeminent position over other foreign languages in enabling global mobility and intercultural communication; however, competence in other foreign languages was also associated with students’ perceptions of destination choice when travelling abroad. Additionally, linguistic competence was linked to students’ perceived willingness and confidence to travel abroad, as well as to their perceived ability to select international travel destinations and to engage confidently in intercultural interactions. The findings indicate that bilingual students, compared with non-bilingual students, place value on language learning for confidence and willingness to travel abroad, highlighting multilingual repertoires as key to students’ capacity for international engagement, growth, intercultural understanding, and global citizenship.